2011
DOI: 10.1007/s00415-010-5895-7
|View full text |Cite
|
Sign up to set email alerts
|

MR neurography of sciatic nerve injection injury

Abstract: We report on magnetic resonance neurography (MRN) as a supplementary diagnostic tool in sciatic nerve injection injury. The object of the study was to test if T2-weighted (w) contrast within the sciatic nerve serves as an objective criterion for sciatic injection injury. Three patients presented with acute sensory and/or motor complaints in the distribution of the sciatic nerve after dorsogluteal injection and underwent MRN covering gluteal, thigh and knee levels. Native and contrast-enhanced T1-w images were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 17 publications
0
19
0
1
Order By: Relevance
“…This decrease of FA values and increase of RD values becomes more conspicuous at the compression site or traction/transection point, as well as in the distal segment, probably due to a Wallerian degeneration mechanism (39). These changes are less evident at proximal segments of the damaged nerve (37). Respecting AD, it might theoretically decrease at the distal segment of a damaged PN as there is interruption of the normal axonal flow (27).…”
Section: Peripheral Nerve Traumatic Lesionsmentioning
confidence: 98%
See 1 more Smart Citation
“…This decrease of FA values and increase of RD values becomes more conspicuous at the compression site or traction/transection point, as well as in the distal segment, probably due to a Wallerian degeneration mechanism (39). These changes are less evident at proximal segments of the damaged nerve (37). Respecting AD, it might theoretically decrease at the distal segment of a damaged PN as there is interruption of the normal axonal flow (27).…”
Section: Peripheral Nerve Traumatic Lesionsmentioning
confidence: 98%
“…However, these parameters may appear insufficient for an adequate nerve evaluation and may not show statistically significant differences between each nerve segments. Thanks to the development of DTN sequences, diverse studies have demonstrated a decrease of FA values, due to the loss of fiber anisotropy and the presence of edema (37). At the same nerve segment, an increase of RD is depicted due to the existence of a facilitated diffusion within the perpendicular plane owing to the disruption of physiological barriers that impeded the motion of water molecules in the short PN axis, mainly myelin sheaths but also endoneurium and perineurium (38) ( Figure 5).…”
Section: Peripheral Nerve Traumatic Lesionsmentioning
confidence: 99%
“…The peroneal division of the sciatic nerve is more frequently injured than the tibial division because of its more lateral position, reduced protective connective tissues, and the relative tethering of the nerve course. 2,13,18 Anatomical variations, such as an absence of (or abnormal subdivision of) the piriformis muscle, or the passing of the peroneal division through the piriformis muscle, may also be associated with nerve injuries after injection. 19,20 The length of the needle, the angle of the needle and the position of the patient during injection (such as lateral decubitus, upright or leaning forward instead of prone) are other major factors in NII.…”
Section: Direct Needle Traumamentioning
confidence: 99%
“…The sciatic nerve derives from the fourth and fifth lumbar and first and second sacral roots, coursing down deeper to the piriformis muscle with anatomical variations. It continues posteromedially to the hip and distally deep in the thigh before dividing into the tibial and common peroneal nerves above the popliteal fossa [2,3].MR imaging patterns vary depending on the muscle denervation stage: acute and subacutely denervated muscles show high SI on fluid-sensitive images and normal SI on T1-weighted images; in chronic denervation, muscle atrophy and fatty infiltration demonstrate high SI on T1-weighted images in association with volume loss [4]. On the other hand, myonecrosis is revealed by high SI on T1-weighted images, heterogeneously high SI on T2-weighted images, and rim enhancement on contrastenhanced images [5].…”
mentioning
confidence: 99%
“…The sciatic nerve derives from the fourth and fifth lumbar and first and second sacral roots, coursing down deeper to the piriformis muscle with anatomical variations. It continues posteromedially to the hip and distally deep in the thigh before dividing into the tibial and common peroneal nerves above the popliteal fossa [2,3].…”
mentioning
confidence: 99%